Effects of moderate altitude on the physical performance of elite female soccer players during an official soccer tournament - Kobal, R.; Loturco, I.; do Carmo, E. C.; Cal Abad, C. C.; Rossetti, M.; Saito, T.; Klosterhoff, R. R.; Barroso, R. (International Journal of Sports Science and Coaching, 2022)
The aim of this study was to investigate the effects of moderate altitude (2800 m) on neuromuscular performance, body-mass, rating of perceived exertion, total quality recovery, and global positioning system-motion variables (distance covered, sprint distance, number of accelerations, and top-speed) during soccer training and official matches. Seventeen professional female soccer players performed vertical jump tests and were weighed over seven days during the altitude acclimatization. Global positioning system-motion variables, rating of perceived exertion, and total quality recovery were assessed over two training sessions at 2800 m and compared to the metrics collected during two sessions at sea level. Global positioning system-motion variables were measured during six official matches played at 2800 m and compared to six matches at sea level. Vertical jump height and body-mass did not change during acclimatization (p > 0.05). Rating of perceived exertion was higher and total quality recovery was lower after training sessions at altitude (p < 0.05). Total distance covered (p = 0.002), total sprint distance (p = 0.016), and total distance covered per minute (p = 0.02) decreased and rating of perceived exertion increased (p = 0.012) in the matches at moderate altitude compared to sea level. No differences were observed for top-speed and acceleration (p > 0.05). These findings suggest that moderate altitude can lead to substantial decreases in the physical performance (especially in total sprint distance), increased rating of perceived exertion, decreased total quality recovery in female players. These occurrences are critical to soccer performance.